Digestibility and performance of steers fed varying inclusions of corn silage and modified distillers grains with solubles to partially replace corn in finishing diets - Burken, D. B. (Transl Anim Sci, 2017)
Two finishing and 1 digestibility experiment evaluated the partial substitution of corn with corn silage and corn modified distillers grains with solubles (MDGS). Steers were used in Exp. 1 (n = 295; 467 ± 52 kg) and Exp. 2 (n = 225; BW = 348 ± 27 kg) in a 2 × 2 + 1 factorial arrangement of treatments with factors including corn silage (15 or 45%) and MDGS (20 or 40%) plus a control diet consisting of 5% cornstalks and 40% MDGS. In Exp. 1, there were tendencies for a corn silage × MDGS interaction for ADG, final BW, and G:F (P ≤ 0.08). In the overall F-test for G:F, there were no differences between the control treatment and 15:20, 15:40, or 45:40 (P ≥ 0.15), however, steers fed the control treatment had increased G:F compared to steers fed 45:20 treatment diets (P = 0.03). In Exp. 2, there were no corn silage × MDGS interactions (P ≥ 0.12). As corn silage increased in the diet, ADG, final BW, and G:F decreased (P ≤ 0.01). As MDGS increased from 20 to 40%, ADG and G:F tended to improve (P ≤ 0.07). In the overall F-test, the control was not different for G:F from 15:20, 45:20, or 45:40 (P ≥ 0.15), but had a 4.8% poorer G:F compared to 15:40 (P < 0.01). In Exp. 3, ruminally fistulated steers (n = 6) were used in a 5 × 6 Latin rectangle design and fed 15 or 45% corn silage with 20 or 40% MDGS as a 2 × 2 factorial. An additional diet consisting of 95% corn silage and 5% supplement was fed. There were no corn silage × MDGS interactions for nutrient intake, total tract digestibility, ruminal pH measurements, acetate: propionate ratio (A:P), or in-situ disappearance data (P ≥ 0.31) for the 2 × 2 factorial. As corn silage increased in the diet, DMI, NDF intake, ruminal pH, A:P, in-situ NDF disappearance of corn bran, and DM disappearance of corn increased (P ≤ 0.09) with decreases in DM and OM digestibility (P ≤ 0.03). As MDGS increased in the diet, there was an increase in NDF intake, total volatile fatty acid concentration, and NDF disappearance of corn bran (P ≤ 0.03) with no differences for any other tested variables (P ≥ 0.13). In general, increasing corn silage in place of corn in finishing diets containing MDGS results in a modest reduction in ADG and G:F with increases in ruminal pH.